Um problema de roteirização de veículos para uma empresa de transportes utilizando um algoritmo genético - Bastos, Marvin Portello (2019)
The present work has the objective of improving the process of vehicle routing for the distribution of cargo destined to clients of a logistics consulting enterprise, a problem known in the literature as the Capacitated Vehicle Routing Problem (CVRP). For this purpose, a genetic algorithm has been programmed in Visual Basic for Applications (VBA) programming language, through software Microsoft Excel®. The tests have been done using three types of operators for the algorithm, comparing the results in relation to the computational time and the efficiency of the routing solutions as a function of the total distance traveled. The comparisons have been made using instances extracted from a real-world problem of a transport company. At the end, the results are shown, where it was verified that the best performances were obtained by the OX1 crossover operator and the method called MIX (hybrid crossover of OX1 and PMX), while PMX showed inefficiency for most cases.